Motor speed reduction methods - Fairchild, Fred J. (My University, 2015)
A.C. motors usually come in standard output speeds of 3600, 1800, 1200 or 900 revolutions per minute (rpms), but the machines they power generally require different input speeds. In order to get to the required input speed for a particular piece of machinery, some type of speed reduction method is required. These reductions in speed are accomplished by using gear reducers, v-belt and sheaves, chain drives with sprockets or combinations of each. In this article, we will focus on gear reducers.
Keywords: Feed processing; A. C. motors; Gear reducers